2019
DOI: 10.1111/gcb.14733
|View full text |Cite
|
Sign up to set email alerts
|

Adapt or die—Response of large herbivores to environmental changes in Europe during the Holocene

Abstract: Climate warming and human landscape transformation during the Holocene resulted in environmental changes for wild animals. The last remnants of the European Pleistocene megafauna that survived into the Holocene were particularly vulnerable to changes in habitat. To track the response of habitat use and foraging of large herbivores to natural and anthropogenic changes in environmental conditions during the Holocene, we investigated carbon (δ13C) and nitrogen (δ15N) stable isotope composition in bone collagen of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 102 publications
2
25
0
Order By: Relevance
“…All recent studies of European bison habitat use we know of suggest that European bison are neither a strict forest specialist nor a strict grassland specialist. For example, European bison have exhibited intermediate diets between true grazers and true browsers, along with high diet plasticity, throughout the Holocene (Bocherens et al ., 2015; Hofman‐Kamińska et al ., 2019), a pattern also found in contemporary herds (Krasińska et al ., 2014). Vegetation reconstructions (Kuemmerle et al ., 2012a) and paleozoological data (Benecke, 2005) suggest that European bison have, for at least 8000 years, been associated with landscapes containing a considerable amount of forest alongside open areas – as they are today (Kuemmerle et al ., 2011; Kuemmerle et al ., 2018).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…All recent studies of European bison habitat use we know of suggest that European bison are neither a strict forest specialist nor a strict grassland specialist. For example, European bison have exhibited intermediate diets between true grazers and true browsers, along with high diet plasticity, throughout the Holocene (Bocherens et al ., 2015; Hofman‐Kamińska et al ., 2019), a pattern also found in contemporary herds (Krasińska et al ., 2014). Vegetation reconstructions (Kuemmerle et al ., 2012a) and paleozoological data (Benecke, 2005) suggest that European bison have, for at least 8000 years, been associated with landscapes containing a considerable amount of forest alongside open areas – as they are today (Kuemmerle et al ., 2011; Kuemmerle et al ., 2018).…”
supporting
confidence: 71%
“…All recent studies of European bison habitat use we know of suggest that European bison are neither a strict forest specialist nor a strict grassland specialist. For example, European bison have exhibited intermediate diets between true grazers and true browsers, along with high diet plasticity, throughout the Holocene(Bocherens et al, 2015;Hofman-Kami nska et al, 2019), a pattern also found in contemporary herds(Krasi nska et al, 2014). Vegetation reconstructions…”
mentioning
confidence: 95%
“…This in turn allows us to consider when environmental changes moved beyond the envelope of natural variability (Ruddiman, 2003;Ruddiman et al, 2016). We focus here on the role of LULCC in the climate system; anthropogenic land-cover change can have broader consequences on other processes and changes, such as erosion and fluvial systems (Downs and Piégay, 2019), biodiversity loss (Barnosky et al, 2012), nutrient cycling (Guiry et al, 2018;McLauchlan et al, 2013), habitat exploitation by megafauna (Hofman-Kamińska et al, 2019) and wider ecosystem functioning (Ellis, 2015;Stephens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to reconstruct the past diet and behaviour of prehistoric bison have to date, for the most part, been conducted as separate biogeochemical studies (e.g., [130,[147][148][149][150]). Without diminishing their significant scientific contribution, we argue that interdisciplinary studies that integrate morphological, isotopic, dietary, and genetic data would contextualise and enhance our knowledge of this enigmatic species complex.…”
Section: Bisonmentioning
confidence: 99%